2021
DOI: 10.1002/jsfa.11574
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a thermophilic protease‐producing strain and its application in solid‐state fermentation of soybean meal

Abstract: BACKGROUND: Thermophiles can thrive at 50-80 °C and produce some enzymes with special promise for biocatalysis. A thermophilic protease-producing strain YYC4 was isolated from Yunyan cigarette and employed in solid-state fermentation (SSF) of unsterilized soybean meal (SBM). RESULTS:The isolate was identified as Bacillus licheniformis based on appearance of colonies, microscopic observation and 16S rDNA sequencing. After SSF, soluble and crude protein contents in SBM increased from 49.24 to 185.73 g kg −1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…However, MC fermented with both L. plantarum and B. subtilis had a higher final pH value than those with single bacterium starter. It was previously reported that the ammonification and mineralization of organic nitrogen via microbial activity promoted the increase in pH value 2 . Therefore, MC with the highest protease activity had a higher pH value than the other treatments.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…However, MC fermented with both L. plantarum and B. subtilis had a higher final pH value than those with single bacterium starter. It was previously reported that the ammonification and mineralization of organic nitrogen via microbial activity promoted the increase in pH value 2 . Therefore, MC with the highest protease activity had a higher pH value than the other treatments.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, the high yield of FAA was probably produced by protease, which was secreted by increasing the amount of bacterium. The application of a protease‐producing strain in FSBM could increase the FAA content 2 . It was concluded that microbes in MC could produce more protease, leading to the increase in the relative content of FAA 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last few years, many extreme enzymes have been studied, including thermophilic ( Dai et al, 2022 ), psychrophilic ( Santiago et al, 2016 ), acidophilic ( Parashar and Satyanarayana, 2018 ), alkalophilic ( Ito et al, 1998 ), halophilic ( Mokashe et al, 2018 ), radiophilic, and barophilic enzymes ( Raddadi et al, 2015 ), but the number of extreme enzymes is currently insufficient to meet growing industrial demands ( Mesbah, 2022 ). Halophilic microorganisms have natural advantages in protease production, and many new extreme enzymes can be developed.…”
Section: Introductionmentioning
confidence: 99%